Modelling the Impact of Oil Price on Food Imports: Case of Oman - Devesh, Sonal; Affendi, Abdullah M. Asrul (International Journal of Energy Economics and Policy, 2021)
The purpose of this paper was to economically analyze and examine the causal relationship between food import bill and certain economic indicators in Oman during the period 1980–2019. The vector error correction model was used to assess the dynamics of food import bill. The finding indicates that food import bill in Oman is positively influenced by the population growth rate, and the GDP per capita, while oil prices showed a negative impact on food import bill. The error correction term suggesting 64 percent of the total disequilibrium in food import bill will be adjusted every year for any shock, justifiable for a dynamic economy like Oman. Keywords: Food import bill; VECM; Granger causality; Oman; Oil Price; GDP; Population growth rate JEL Classifications: C10; C51; C82; C87 DOI: https://doi.org/10.32479/ijeep.11363